Implementasi Program Tahfidz Al-Qur’an dalam Pembentukan Karakter Religius di MTs At-Tahzib dan MTs Al-Ishlahuddiny, Lombok Barat - Abd Samad; Lalu Supriadi bin Mujib; Abdul Malik (LP2M STIT Palapa Nusantara, 2023)
The rise of the phenomenon of students' moral deviation seen in the millennial era is really concerning to the world of education so that one of the efforts to shape the religious character of students is through the tahfidz al-Qur'an program. . This study aims to determine the implementation of the Al-Qur'an tahfidz program and the formation of the religious character of students. An important aspect of this research is the implementation of the tahfidz Al-Qur'an program and the formation of religious character which includes: Methods, stages, indicators and supporting and inhibiting factors for the formation of the tahfidz al-Qur'an program internally and externally at MTs At-Tahzib and MTs Al -Ishlahuddiny. This study uses a qualitative approach. The data collection method used is the method of observation, interviews and documentation. Based on the research results, (1)The implementation of the Al-Qur'an tahfidz program is good and running smoothly. (2)The formation of the religious character of students is said to be good by applying exemplary methods, habituation, advice and methods of reward and punishment. The stages are the stages of knowledge, awareness, practice, habituation and maintenance of religious character values. Indicators of forming religious character include: akhlakul karimah, speaking polite words, praying in congregation, praying dhuha, praying before and after learning, saying greetings when meeting, morning imtaq activities and reading yasin and ratib Friday evening. Internal supporting factors: health, intelligence and motivation. External factors: cooperation of all parties, competent tahfidz teachers, time management, government response, internal inhibiting factors: Lazy, impatient, hopeless, difficult to manage time and often forget. External factors: economic capacity and material density.